Perilaku Investor Muslim Dalam Bertransaksi Saham di Pasar Modal - Agustin, Pramita; Mawardi, Imron (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
This research aims to know the muslim investor behavior in a stock transaction in capital market. This research used the qualitative approach, using the case study method by basing on the theory of behavioral finance.Data collection using a purposive sampling technique to determine informants amounted to five muslim investors who at least has a two year stock transaction to be interviewed in depth, observed and evaluated the data by performing a triangulation.The results of this research have findings that muslim investor behavior in a stock transaction is divided into two point of view that is, investors who consider religion in their investment decisions and the invetor did not consider religion in their investment decisions. Investors who consider religion in their investment decisions preferring stock composition of the incoming Sharia index list and nature of investments tend to be long term. Investors who do not consider religion in choosing his investment decision stock blends well in the Shariahcompliantindex or not. The nature of investment investors who did not consider the shortterm nature of the religion.